Steel sheet and plated steel sheet

By containing Si and Al in a high-strength steel plate and forming a ferrite phase layer with low C concentration after annealing at high dew point, the problems of liquid metal brittleness and hydrogen embrittlement cracks are solved, and the high LME resistance and dehydrogenation of the steel plate are achieved.

CN119836486APending Publication Date: 2025-04-15NIPPON STEEL CORPORATION
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380064190.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-06
Filing Date
2023-09-06
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The prior art is difficult to effectively prevent liquid metal brittle (LME) cracks and hydrogen embrittlement cracks, especially during welding of high-strength steel plates.

Method used

By containing Si and Al in a large amount of the steel plate and controlling the surface state during high dew point annealing, a ferrite phase layer with low C concentration is formed, thereby inhibiting LME cracks and promoting hydrogen dehydrogenation.

Benefits of technology

The high LME resistance and dehydrogenation of the steel plate are achieved, and the welding quality and overall performance of the steel plate are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119836486A_ABST
    Figure CN119836486A_ABST
Patent Text Reader

Abstract

The present invention addresses the problem of providing a steel sheet and a plated steel sheet having high LME resistance and dehydrogenation properties. A steel sheet and a plated steel sheet according to the present invention are characterized by having a prescribed chemical composition, having a depth of 10 [mu] m or more at which the C concentration measured by GDS is 0.05% or less in the depth direction from the surface of the steel sheet, and having a thickness of 20 [mu] m or more at which the area ratio of a ferrite phase is 90% or more in the depth direction from the surface of the steel sheet. The surface roughness Ra of the steel sheet is 3.0 [mu] m or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a steel sheet and a plated steel sheet, and more particularly to a steel sheet and a plated steel sheet having high LME resistance and dehydrogenation resistance. Background Art

[0002] In recent years, the strength of steel sheets used in various fields such as automobiles, home appliances, and building materials has been increased. For example, in the automobile field, the use of high-strength steel sheets has increased for the purpose of reducing the weight of the vehicle body in order to improve fuel efficiency.

[0003] In the case of welding of zinc-plated steel sheets, especially high-strength steel sheets, a reduction in weldability due to liquid metal embrittlement (LME) cracks may become a problem, as described in Patent Document 1, for example. It is believed that LME cracks are generated by the following steps: the surface layer of the steel sheet is transformed into austenite during welding, and the molten zinc that penetrates the grain boundaries makes the steel sheet embrittled, and further tensile stress is applied to the steel sheet during welding.

[0004] In addition, as disclosed in Non-Patent Document 1, regarding LME cracking, it is known that the LME sensitivity of the grain boundary of the ferrite phase is lower than that of the austenite grain boundary.

[0005] It should be noted that Patent Document 2 discloses a steel plate having 3000 to 6000 cracks / mm2 on the surface layer of the steel plate as a steel plate having improved weldability by suppressing LME cracks. 2 The Si oxide particles with a particle size of 20 nm or more exist in a number density and with an appropriate particle size distribution.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: International Publication No. 2019 / 116531

[0009] Patent Document 2: International Publication No. 2020 / 218575

[0010] Non-patent literature

[0011] Non-patent document 1: Influence of the starting microstructure of an advancedhigh strength steel on the characteristics of Zn-Assisted liquid metalembrittlement, D.Bhattacharya et.al., Materials Science and Engineering: A, Vol.804.2021 Summary of the invention

[0012] Problems to be solved by the invention

[0013] In order to prevent LME cracks, it is effective to suppress the intrusion of Zn and the like contained in the coating into the steel sheet after austenite transformation. In this regard, there is room for improvement.

[0014] In addition, it is known that if a high-strength steel plate is exposed to an atmospheric corrosion environment with large changes in temperature and humidity, hydrogen generated during the corrosion process will invade the steel. The hydrogen invading the steel segregates at the martensite grain boundaries of the steel structure, embrittles the grain boundaries, and thus becomes the cause of cracks in the steel plate. The phenomenon of cracks caused by hydrogen intrusion is called hydrogen embrittlement cracking (delayed fracture), which often becomes a problem during steel plate processing. In order to prevent this situation, it is effective to promote dehydrogenation from the steel plate to the atmosphere when hydrogen intrudes into the steel plate.

[0015] In view of such actual conditions, an object of the present invention is to provide a steel sheet and a plated steel sheet having high LME resistance and dehydrogenation resistance.

[0016] Means for solving problems

[0017] The present inventors have conducted intensive studies on means for solving the above-mentioned problems. As a result, they have found that by making a steel sheet contain a large amount of Si and Al, making the steel sheet in an appropriate surface state and performing high dew point annealing, the surface layer of the steel sheet is decarburized, and the ferrite (α) phase is stabilized, and the surface layer of the steel sheet is covered with a ferrite phase with a low solid solution amount of C, and as a result, LME can be suppressed. Furthermore, they have found that by covering the surface layer of the steel sheet with a ferrite phase with a low solid solution amount of C, even when hydrogen invades the steel sheet, dehydrogenation from the steel sheet to the atmosphere is promoted.

[0018] The present invention has been completed as a result of further studies based on the above findings, and the gist of the present invention is as follows.

[0019] (1) A steel sheet having a tensile strength of 780 MPa or more, characterized in that the chemical composition comprises, in mass%, C: 0.05-0.40%, Si: 0.7-3.0%, Mn: 0.1-5.0%, sol.Al: 0.7-2.0%, P: 0.0300% or less, S: 0.0300% or less, N: 0.0100% or less, B: 0-0.010%, Ti: 0-0.150%, Nb: 0-0.150%, V: 0-0.150%, Cr: 0-2.00%, Ni: 0-2.00%, Cu: 0-2.00%, Mo: 0-1.0 0%, W: 0-1.00%, Ca: 0-0.100%, Mg: 0-0.100%, Zr: 0-0.100%, Hf: 0-0.100%, REM: 0-0.100%, the remainder is Fe and impurities, the total value of Si and sol.Al contents is 1.8% or more, the depth at which the C concentration is less than 0.05% as measured by GDS is 10 μm or more in the depth direction from the surface of the steel plate, the thickness of the layer in which the area ratio of the ferrite phase is 90% or more in the depth direction from the surface of the steel plate is 20 μm or more, and the surface roughness of the steel plate is 3.0 μm or less in terms of Ra.

[0020] (2) The steel sheet according to (1) above, wherein the depth in the depth direction from the surface of the steel sheet where the C concentration measured by GDS is 0.05% or less is 20 μm or more.

[0021] (3) The steel sheet according to (1) above, wherein the thickness of the layer having an area ratio of ferrite phase of 90% or more in the depth direction from the surface of the steel sheet is 30 μm or more.

[0022] (4) A steel plate according to (1) above, characterized in that, in the depth direction from the surface of the steel plate, the depth at which the C concentration measured by GDS is less than 0.05% is greater than 20 μm, and in the depth direction from the surface of the steel plate, the thickness of the layer in which the area ratio of the ferrite phase is greater than 90% is greater than 30 μm.

[0023] (5) An alloyed hot-dip galvanized steel sheet (also referred to as an alloyed hot-dip galvanized steel sheet), characterized in that at least a portion of the surface of the steel sheet described in any one of (1) to (4) is provided with an alloyed hot-dip galvanized layer, wherein the coating contains, in terms of mass%, 0 to 1.5% Al and 3 to 15% Fe, with the remainder being Zn and impurities.

[0024] (6) The galvannealed steel sheet according to (5) above, wherein the roughness of the interface between the steel sheet and the galvannealed layer in the cross section of the galvannealed steel sheet is 2.0 μm or less in terms of Ra.

[0025] Effects of the Invention

[0026] According to the present invention, a steel sheet and a plated steel sheet having high LME resistance and dehydrogenation resistance can be obtained. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is a diagram showing a layered ferrite phase formed in the surface layer of the steel sheet of the present invention.

[0028] Figure 2 It is a figure explaining the evaluation of LME resistance in Examples. DETAILED DESCRIPTION

[0029] The present invention will be described below. The present invention is not limited to the following embodiments. First, an overview of improving LME resistance in the steel sheet and plated steel sheet of the present invention will be described.

[0030] LME cracks are generated by the following steps: during spot welding, the surface layer of the steel plate is heated and the steel plate structure of the surface layer is transformed into austenite, and the molten plating enters the steel plate structure along the grain boundaries of the austenite, thereby embrittlement of the grain boundaries. It is believed that tensile stress is applied to the steel plate during welding, so LME cracks are generated. The steel plate of the present invention improves LME resistance by forming a structure in the surface layer. It should be noted that in this specification, the surface layer of the steel plate refers to the range from the outermost surface of the steel plate to a depth of 100 μm.

[0031] If the C element is contained in the surface layer of the steel plate, LME cracks are likely to occur, so suppressing the C concentration in the surface layer of the steel plate to a low level is effective in preventing LME cracks. Generally, when the steel plate is heated as in annealing, external oxidation occurs and oxides (scale) are formed on the surface of the steel plate, so decarburization is difficult. Therefore, it is difficult to reduce the C concentration in the surface layer of the steel plate. On the other hand, in the steel plate of the present invention, in the depth direction from the surface of the steel plate, an area where the C concentration measured by GDS is less than 0.05% exists more than 10 μm from the surface of the steel plate. This means that the concentration of C, an element that is likely to cause LME, is low in the surface layer of the steel plate.

[0032] However, it is considered that even when the C concentration in the surface layer of the steel plate is low, if there is a lot of austenite (γ) with high LME sensitivity in the structure of the surface layer, the LME resistance may be reduced. Therefore, in the steel plate of the present embodiment, the thickness of the region where the area ratio of the ferrite phase is 90% or more in the depth direction from the surface of the steel plate is set to 20 μm or more. In addition, the steel plate of the present invention contains a large amount of Si, which is previously known to reduce the LME resistance when contained in steel. This is because the research results of the present inventors found that, contrary to previous views, by making the steel plate contain a large amount of Si and sol.Al at the same time, the LME resistance is improved.

[0033] In the present invention, a strong strain is imparted to the surface layer without increasing the surface roughness of the steel sheet, and the steel sheet is annealed at a high dew point. As a result, oxygen diffuses into the interior of the steel sheet to form internal oxides, and the formation of external oxides can be suppressed. It is believed that this is because the C concentration in the surface layer of the steel sheet can be reduced, and the ferrite can be stabilized by the effect of the combined addition of Si and sol.Al.

[0034] That is, the steel sheet of the present invention forms a layer with a low C concentration and a high ferrite area ratio in the surface layer of the steel sheet by combining the effects of high Si and sol.Al contents, imparting strain to the surface layer before annealing, and controlling the dew point during annealing, thereby improving LME resistance.

[0035] Hereinafter, the present invention will be described in detail.

[0036] First, the chemical composition of the steel plate is described. Hereinafter, "%" of the chemical composition means "mass %". In addition, in the numerical range of the chemical composition, the numerical range expressed by "to" means a range including the numerical values ​​recorded before and after "to" as the lower limit and upper limit.

[0037] (C: 0.05~0.40%)

[0038] C (carbon) is an element that ensures the strength of steel. Since the present invention aims to obtain a tensile strength of 780 MPa or more, a balance with weldability must be considered, and in order to prevent the C concentration in the surface layer of the steel plate from becoming too high, the C content is set to 0.05-0.40%. If the C content is too high, the C concentration in the surface layer will not decrease and the ferrite fraction will not increase even through the high dew point annealing described later. The C content can be 0.07% or more, 0.10% or more, or 0.12% or more. The C content can be 0.35% or less, 0.30% or less, or 0.25% or less.

[0039] (Si: 0.7~3.0%, sol.Al: 0.7~2.0%, Si+sol.Al≥1.8%)

[0040] Si (silicon) is an element that promotes ferrite stabilization and decarburization by being added in combination with Al (aluminum). In order to obtain the effect of improving LME resistance, Si: 0.7-3.0%, sol.Al: 0.7-2.0%, and further, the total content of Si and sol.Al is 1.8% or more. This is because, by making the contents of Si and sol.Al satisfy such a numerical range, decarburization of the surface layer of the steel plate can be promoted in the heat treatment of the manufacturing process of the steel plate of this embodiment, and the ferrite of the surface layer can be stabilized. Sol.Al refers to acid-soluble Al that does not become an oxide such as Al2O3 and is soluble in acid, and is obtained by subtracting the Al measured by the insoluble residue on the filter paper generated in the process of analyzing Al. The content of Si can be 0.8% or more, 0.9% or more, or 1.0% or more. The content of Si can be 2.8% or less, 2.5% or less, or 2.0% or less. The content of sol.Al can be 0.8% or more, 0.9% or more, or 1.0% or more. The content of sol.Al may be 1.8% or less, 1.6% or less, or 1.5% or less. The total content of Si and sol.Al may be 1.9% or more, or 2.0% or more.

[0041] (Mn: 0.1~5.0%)

[0042] Mn (manganese) is an element effective in improving the strength of steel by obtaining a hard structure. Considering the balance between the strength of steel and the reduction in workability caused by Mn segregation, the Mn content is set to 0.1-5.0%. The Mn content may be 0.5% or more, 1.0% or more, or 1.5% or more. The Mn content may be 4.5% or less, 4.0% or less, or 3.5% or less.

[0043] (P: 0.0300% or less)

[0044] P (phosphorus) is usually an impurity contained in steel. When the content of P exceeds 0.0300%, weldability may be reduced. Therefore, the content of P is set to 0.0300% or less. The content of P may be 0.0200% or less, 0.0100% or less, or 0.0050% or less. It is preferred that P is not contained, and the lower limit of the content of P is preferably 0%. From the viewpoint of dephosphorization cost, the content of P may be more than 0%, 0.0001% or more, or 0.0005% or more.

[0045] (S: 0.0300% or less)

[0046] S (sulfur) is usually an impurity contained in steel. When the S content exceeds 0.0300%, the weldability may be reduced, and the precipitation amount of MnS may increase, and the processability such as bendability may be reduced. Therefore, the S content is set to 0.0300% or less. The S content may be less than 0.0100%, less than 0.0050%, less than 0.0030%, less than 0.0020% or less than 0.0010%. It is preferred that S is not contained, and the lower limit of the S content is 0%. From the perspective of desulfurization cost, the S content may be more than 0%, more than 0.0001% or more than 0.0005%.

[0047] (N: 0.0100% or less)

[0048] N (nitrogen) is usually an impurity contained in steel. When the N content exceeds 0.0100%, weldability may be reduced. Therefore, the N content is set to 0.0100% or less. The N content can be 0.0080% or less, 0.0050% or less, 0.0030% or less, 0.0020% or less, or 0.0010% or less. It is preferred that N is not contained, and the lower limit of the N content is 0%. From the viewpoint of manufacturing cost, the N content can be more than 0%, 0.0001% or more, 0.0002% or more, 0.0003% or more, or 0.0005% or more.

[0049] (B: 0~0.010%)

[0050] B (boron) is an element that improves hardenability and contributes to the improvement of strength, and segregates at grain boundaries to strengthen the grain boundaries and improve toughness, so B can also be contained as needed. Since it is not an essential element, the lower limit of the B content is 0%. Although this effect can be obtained even with a trace amount, the B content when contained is preferably 0.0001% or more. The B content can be 0.0002% or more, 0.0003% or more, 0.0005% or more, 0.0007% or more, or 0.0010% or more. On the other hand, from the viewpoint of ensuring sufficient toughness, the B content is set to 0.010% or less. The B content can be 0.0080% or less, 0.0060% or less, 0.0050% or less, 0.0040% or less, or 0.0030% or less.

[0051] (Ti: 0~0.150%)

[0052] Ti (titanium) is an element that precipitates in the form of TiC during the cooling of steel and contributes to the improvement of strength, so Ti can be contained as needed. Since it is not an essential element, the lower limit of the Ti content is 0%. Although this effect can be obtained by containing a trace amount, the Ti content when contained is preferably 0.0001% or more. The Ti content can be 0.0002% or more, 0.0003% or more, 0.0005% or more, 0.0007% or more, or 0.0010% or more. On the other hand, if it is contained excessively, coarse TiN may be generated, resulting in impaired toughness, so the Ti content is set to 0.150% or less. The Ti content can be 0.1000% or less, 0.0500% or less, 0.0300% or less, 0.0200% or less, 0.0100% or less, 0.0050% or less, or 0.0030% or less.

[0053] (Nb: 0~0.150%)

[0054] Nb (niobium) is an element that contributes to the improvement of strength by improving hardenability, so Nb can be contained as needed. Since it is not an essential element, the lower limit of the Nb content is 0%. Although this effect can be obtained even with a trace amount, the Nb content when contained is preferably 0.001% or more. The Nb content can be 0.002% or more, 0.003% or more, 0.005% or more, or 0.008% or more. On the other hand, from the viewpoint of ensuring sufficient toughness, the Nb content is set to 0.150% or less. The Nb content can be 0.100% or less, 0.060% or less, 0.050% or less, 0.040% or less, or 0.030% or less.

[0055] (V: 0~0.150%)

[0056] V (vanadium) is an element that contributes to the improvement of strength by improving hardenability, so V can also be contained as needed. Since it is not an essential element, the lower limit of the V content is 0%. Although this effect can be obtained even with a trace amount, the V content when contained is preferably 0.001% or more. The V content can be 0.002% or more, 0.003% or more, or 0.005% or more. On the other hand, from the viewpoint of ensuring sufficient toughness, the V content is set to 0.150% or less. The V content can be 0.100% or less, 0.060% or less, 0.050% or less, 0.040% or less, or 0.030% or less.

[0057] (Cr: 0~2.00%)

[0058] Cr (chromium) is effective in improving the hardenability of steel and the strength of steel, so Cr can be contained as needed. Since it is not an essential element, the lower limit of the Cr content is 0%. Although this effect can be obtained even with a trace amount, the Cr content when contained is preferably 0.001% or more. The Cr content can be 0.01% or more, 0.02% or more, 0.03% or more, 0.05% or more, or 0.08% or more. On the other hand, if it is contained excessively, a large amount of Cr carbides will be formed, which may impair the hardenability, so the Cr content is set to 2.00% or less. The Cr content can be 1.80% or less, 1.50% or less, 1.20% or less, 1.00% or less, 0.70% or less, 0.50% or less, or 0.30% or less.

[0059] (Ni: 0~2.00%)

[0060] Ni (nickel) is effective for improving the hardenability of steel and the strength of steel, so Ni can also be contained as needed. Since it is not an essential element, the lower limit of the content of Ni is 0%. Although this effect can be obtained by containing in trace amounts, the content of Ni when contained is preferably more than 0.001%. The content of Ni can be more than 0.01%, more than 0.02%, more than 0.03%, more than 0.05% or more than 0.07%. On the other hand, excessive addition of Ni can lead to rising costs, so the content of Ni is set to less than 2.00%. The content of Ni can be less than 1.80%, less than 1.50%, less than 1.20%, less than 1.00%, less than 0.80%, less than 0.50%, less than 0.30% or less than 0.20%.

[0061] (Cu: 0-2.00%)

[0062] Cu (copper) is effective for improving the hardenability of steel and the strength of steel, so Cu can also be contained as needed. Since it is not an essential element, the lower limit of the Cu content is 0%. Although this effect can be obtained by containing a trace amount, the Cu content when contained is preferably 0.0001% or more. The Cu content can be 0.0002% or more, 0.0003% or more, or 0.0005% or more. On the other hand, from the viewpoint of suppressing the reduction of toughness and the cracking of the slab after casting, the Cu content is set to 2.00% or less. The Cu content can be 1.8000% or less, 1.5000% or less, 1.2000% or less, 1.0000% or less, 0.5000% or less, 0.1000% or less, 0.0500% or less, 0.0100% or less, 0.0050% or less, 0.0030% or less, or 0.0020% or less.

[0063] (Mo: 0~1.00%)

[0064] Mo (molybdenum) is effective for improving the hardenability of steel and the strength of steel, so Mo can be contained as needed. Since it is not an essential element, the lower limit of the Mo content is 0%. Although this effect can be obtained even with a trace amount, the Mo content when contained is preferably 0.001% or more. The Mo content can be 0.01% or more, 0.02% or more, 0.03% or more, 0.05% or more, or 0.08% or more. On the other hand, from the viewpoint of suppressing the reduction of toughness, the Mo content is set to 1.00% or less. The Mo content can be 0.90% or less, 0.70% or less, 0.50% or less, or 0.30% or less.

[0065] (W: 0~1.00%)

[0066] W (tungsten) is effective for improving the hardenability of steel and the strength of steel, so W can also be contained as needed. Since it is not an essential element, the lower limit of the W content is 0%. Although this effect can be obtained even with a trace amount, the W content when contained is preferably 0.001% or more. The W content can be 0.002% or more, 0.003% or more, or 0.004% or more. On the other hand, from the viewpoint of suppressing the reduction of toughness, the W content is set to 1.00% or less. The W content can be 0.900% or less, 0.700% or less, 0.500% or less, 0.300% or less, 0.100% or less, 0.050% or less, 0.030% or less, or 0.020% or less.

[0067] (Ca: 0~0.100%)

[0068] Ca (calcium) is an element having the following effects: it helps to control inclusions, especially fine dispersion of inclusions, and improves toughness, so Ca can be contained as needed. Since it is not an essential element, the lower limit of the Ca content is 0%. Although this effect can be obtained even with a trace amount, the Ca content when contained is preferably 0.0001% or more. The Ca content can be 0.0002% or more, 0.0003% or more, or 0.0004% or more. On the other hand, if it is contained excessively, the deterioration of the surface properties sometimes becomes obvious, so the Ca content is set to 0.100% or less. The Ca content can be 0.0800% or less, 0.0500% or less, 0.0100% or less, 0.0050% or less, 0.0030% or less, 0.0020% or less, or 0.0010% or less.

[0069] (Mg: 0~0.100%)

[0070] Mg (magnesium) is an element having the following effects: it helps to control inclusions, especially fine dispersion of inclusions, and improves toughness, so Mg can be contained as needed. Since it is not an essential element, the lower limit of the Mg content is 0%. Although this effect can be obtained even with a trace amount, the Mg content when contained is preferably 0.0001% or more. The Mg content can be 0.0002% or more, 0.0003% or more, 0.0005% or more, or 0.0008% or more. On the other hand, if it is contained excessively, the deterioration of the surface properties sometimes becomes obvious, so the Mg content is set to 0.100% or less. The Mg content can be 0.090% or less, 0.080% or less, 0.050% or less, 0.010% or less, 0.005% or less, or 0.003% or less.

[0071] (Zr: 0~0.100%)

[0072] Zr (zirconium) is an element having the following effects: it helps to control inclusions, especially fine dispersion of inclusions, and improves toughness, so Zr can be contained as needed. Since it is not an essential element, the lower limit of the Zr content is 0%. Although this effect can be obtained even with a trace amount, the Zr content when contained is preferably 0.001% or more. The Zr content can be 0.002% or more, 0.003% or more, 0.005% or more, or 0.010% or more. On the other hand, if it is contained excessively, the deterioration of the surface properties sometimes becomes obvious, so the Zr content is set to 0.100% or less. The Zr content can be 0.080% or less, 0.050% or less, 0.040% or less, or 0.030% or less.

[0073] (Hf: 0~0.100%)

[0074] Hf (Hafnium) is an element having the following effects: it helps to control inclusions, especially fine dispersion of inclusions, and improves toughness, so Hf can be contained as needed. Since it is not an essential element, the lower limit of the Hf content is 0%. Although this effect can be obtained even with a trace amount, the Hf content when contained is preferably 0.0001% or more. The Hf content can be 0.0002% or more, 0.0003% or more, 0.0005% or more, or 0.0008% or more. On the other hand, if it is contained excessively, the deterioration of the surface properties sometimes becomes obvious, so the Hf content is set to 0.100% or less. The Hf content is 0.050% or less, 0.030% or less, 0.010% or less, 0.005% or less, or 0.003% or less.

[0075] (REM: 0~0.100%)

[0076] REM (rare earth element) is an element having the following effects: it helps to control inclusions, especially fine dispersion of inclusions, and improves toughness, so REM can also be contained as needed. Since it is not an essential element, the lower limit of the REM content is 0%. Although this effect can be obtained even with a trace amount, the REM content when contained is preferably 0.0001% or more. The REM content can be 0.0003% or more, 0.0005% or more, or 0.0007% or more. On the other hand, if it is contained excessively, the deterioration of the surface properties sometimes becomes obvious, so the REM content is set to 0.100% or less. The REM content can be 0.0500% or less, 0.0300% or less, 0.0100% or less, 0.0050% or less, 0.0030% or less, or 0.0020% or less. It should be noted that REM is the abbreviation of Rare Earth Metal, which refers to an element belonging to the lanthanide series. REMs are usually added in the form of misch metals.

[0077] In the steel sheet of the present invention, the remainder other than the above chemical components is composed of Fe and impurities. Here, impurities refer to components mixed into the steel sheet due to various reasons in the manufacturing process, such as raw materials such as ore and waste, when the steel sheet is manufactured industrially, and are contained within a range that does not adversely affect the LME resistance and dehydrogenation properties of the steel sheet of the present invention, that is, within a range that can obtain the LME resistance and dehydrogenation properties required for the steel sheet of the present invention.

[0078] The chemical composition of the steel plate can be analyzed by an elemental analysis method known to those skilled in the art, for example, by inductively coupled plasma mass spectrometry (ICP-MS). C and S can be measured by combustion-infrared absorption method, and N can be measured by inert gas melting-thermal conductivity method. These analyses can be performed using samples collected from the steel plate according to the method of JIS G0417:1999.

[0079] Next, the surface layer portion of the steel plate will be described.

[0080] [C concentration]

[0081] In the steel sheet of the present invention, the depth at which the C concentration is 0.05% or less as measured by GDS (glow discharge spectrometry) is 10 μm or more in the depth direction from the surface of the steel sheet.

[0082] Since the sensitivity to LME decreases when the C concentration decreases, the C concentration in the surface layer is low, thereby improving the LME resistance. In addition, C is an austenite stabilizing element, so by reducing it, the ferrite phase with low LME sensitivity described later is stabilized. Furthermore, if the C in the surface layer is small, the hydrogen intruding into the steel is easily detached, and the dehydrogenation property is improved. It is speculated that this is because the presence of C as an intrusive element in the ferrite phase is small, so hydrogen can easily pass through.

[0083] Such a surface structure can be obtained by setting the chemical composition of the steel sheet to a component containing a large amount of Si and Al as described above and performing a heat treatment described later.

[0084] If the depth at which the C concentration is 0.05% or less is 10 μm or more, the effect of improving LME resistance can be obtained, so the upper limit of the depth is not particularly limited. For example, it can be 50 μm or less, 40 μm or less, or 30 μm or less. The depth at which the C concentration is 0.05% or less is preferably 20 μm or more.

[0085] GDS measurement was performed 5 times in the thickness direction, and the average value was taken as the C concentration. The measurement conditions are as follows. The starting point of the "depth" is the surface of the steel plate for unplated steel plates and the interface between the steel plate and the plating layer for plated steel plates. The interface between the steel plate and the plating layer is set to the position where the Fe concentration measured by the GDS measurement method becomes 93% of the Fe concentration at a depth of 150 μm.

[0086] Apparatus: High frequency glow discharge luminescence analysis apparatus (manufactured by LECO Japan Contract Co., Ltd., model "GDS850A")

[0087] Ar gas pressure: 0.3MPa

[0088] Anode diameter: 4mmφ

[0089] RF output: 30W

[0090] Measuring time: 200 to 1500 seconds

[0091] [Ferrite phase]

[0092] In the steel sheet of the present invention, the thickness of the layer having an area ratio of ferrite phase of 90% or more in the depth direction from the surface of the steel sheet is 20 μm or more. Figure 1 An example of a microstructure photograph obtained by SEM near the surface layer of the steel plate of the present invention is shown. Figure 1 It is a cross section of the steel plate in the thickness direction, and the upper side of the figure is the surface of the steel plate. Figure 1 The surface layer of the steel sheet in the embodiment of the present invention contains a layer with a low C concentration and a ferrite phase area ratio of more than 90%. The interior of the steel sheet is a structure mainly composed of martensite and ferrite. Figure 1In the steel sheet, a layer having a ferrite phase area ratio of 90% or more exists in the surface layer with a thickness of 40 μm.

[0093] It is known that the LME sensitivity of the grain boundary of the ferrite phase is lower than that of the γ (austenite) grain boundary (for example, Non-Patent Document 1). Therefore, by making the structure mainly composed of the ferrite phase thicker in the surface layer of the steel plate, LME is not easily generated even when the plating is melted, and the LME resistance can be improved. Such a surface structure can be obtained by setting the chemical composition of the steel plate to a component containing a large amount of Si and Al as described above and performing the heat treatment described later.

[0094] If the thickness of the region where the area ratio of the ferrite phase is 90% or more is 20 μm or more, the effect of improving the LME resistance can be obtained, so the upper limit of the thickness is not particularly limited. For example, it can be set to 100 μm or less, 80 μm or less, or 60 μm or less. The thickness of the region where the area ratio of the ferrite phase is 90% or more is preferably 30 μm or more.

[0095] The thickness of the area where the area ratio of the ferrite phase is more than 90% can be distinguished from martensite, bainite, and ferrite according to their organizational morphology by etching the L section of the steel plate with nitric alcohol and observing it with SEM. Specifically, the L-direction section is ground, and after mirror polishing, it is etched with nitric alcohol etching solution to make the steel structure corroded and visible. Then, secondary electron images of 5 fields of view are taken at equal intervals at a magnification of 1500 times in a range of 500μm in the depth direction based on the steel surface. The area ratio of the ferrite phase is measured by the point counting method (according to ASTM E 562), and the thickness of the area where the area ratio of the ferrite phase is more than 90% is measured according to each photographed field of view.

[0096] Here, the area ratio of the ferrite phase refers to the area ratio obtained by observing the L cross section. When the C cross section is partially observed in the middle of the thickness direction, even if there is a portion where the area ratio of the ferrite phase is less than 90%, there is no problem as long as the area ratio of the ferrite phase in the L cross section to a depth of 20 μm is 90% or more. More specific area ratios are as follows.

[0097] The ferrite area ratio is measured as described below. Along an imaginary line on the surface of the steel plate orthogonal to the rolling direction of the steel plate, the steel plate is cut perpendicularly relative to the plate thickness direction, i.e., the surface of the steel plate, and a test piece is cut out. Next, after mirror polishing the cross section orthogonal to the rolling direction of the steel plate, the steel structure is visualized using a nitric acid ethanol solution, and a secondary electron image is taken using an electric field emission type scanning electron microscope. The range of the observed field of view is set to the surface of the steel plate in the case of a non-plated steel plate, and is set to the range from the interface between the steel plate and the coating to 500 μm in the depth direction in the case of a plated steel plate, and 5 fields of view are observed at equal intervals. For the obtained tissue photograph, the fraction of each tissue is calculated by the point counting method. First, a grid with equal intervals is drawn on the tissue photograph. Next, it is determined whether the structure of each grid point corresponds to tempered martensite, pearlite, ferrite, primary martensite or retained austenite, or bainite. The number of grid points corresponding to each tissue is obtained and divided by the total number of grid points, thereby determining the fraction of each tissue. In the present invention, the grid interval is set to 2 μm×2 μm, and the total number of grid points is set to 1500 points.

[0098] The criteria for judging pearlite, ferrite, martensite, and bainite are as follows. The region where the lower structure (lath boundary, lath bundle boundary) is present in the grain and carbides are precipitated with multiple variants is judged as tempered martensite. In addition, the region where cementite is precipitated in lamellar form is judged as pearlite. The region with low brightness and no lower structure is confirmed is judged as ferrite. The region with high brightness and the lower structure not revealed by etching is judged as primary martensite or residual austenite. The region that does not meet any of the above is judged as bainite. Simply put, if it is distinguished from ferrite and other structures, the area ratio of the ferrite phase can be calculated.

[0099] [Surface roughness]

[0100] The surface roughness of the steel sheet of the present invention is 3.0 μm or less in terms of the arithmetic mean height Ra defined in JIS B0601: 2013. If the roughness increases, cracks are easily generated due to stress concentration, so LME resistance decreases. The surface roughness may be 2.5 μm or less or 2.0 μm or less.

[0101] [Tensile strength]

[0102] The present invention suppresses LME generated by a high-strength steel plate, so the steel plate of the present invention is high-strength. Specifically, it has a tensile strength of 780 MPa or more. The upper limit of the tensile strength is not particularly limited, and from the viewpoint of ensuring toughness, for example, it can be 2000 MPa or less. The tensile strength can be measured by collecting a JIS No. 5 tensile test piece with a direction perpendicular to the rolling direction as the length direction in accordance with JIS Z2241: 2011. The tensile strength can be 880 MPa or more, 980 MPa or more, 1080 MPa or more, or 1180 MPa or more. The tensile strength can be 1900 MPa or less, or 1800 MPa or less.

[0103] <Plated Steel Sheet>

[0104] The plated steel sheet of the present invention has an alloyed hot-dip galvannealed layer on the steel sheet of the present invention. The plated layer is formed on at least a portion of the surface of the steel sheet, and may be formed on one surface or both surfaces of the steel sheet.

[0105] [Chemical composition of the coating]

[0106] The chemical composition of the alloyed hot-dip galvannealing in the present invention is described. Unless otherwise specified, the "%" related to the content of the element means "mass %". In the numerical range of the chemical composition of the coating, the numerical range represented by "to" means the range including the numerical values ​​recorded before and after "to" as the lower limit and upper limit unless otherwise specified.

[0107] (Al: 0-1.5%)

[0108] Al is an element that is included or alloyed with Zn to improve the corrosion resistance of the coating, so Al can be contained as needed. Therefore, the content of Al can be 0%. In order to form a coating containing Zn and Al, the content of Al can be 0.01% or more, or 0.1% or more. When the Al in the coating is in the range of 0.3 to 1.5%, due to the effect of Al, the speed of Zn invading the steel grain boundary is greatly reduced, and the LME resistance can be improved. Therefore, from the viewpoint of improving the LME resistance, the Al in the coating is preferably 0.3 to 1.5%.

[0109] (Fe: 3-15%)

[0110] Fe is contained in the coating layer by diffusion from the steel sheet when the plated steel sheet is heat-treated after forming a coating layer containing Zn on the steel sheet. The content of Fe may be 3.0% or more, 4.0% or more, or 5.0% or more. On the other hand, the content of Fe may be 15.0% or less, for example, 12.0% or less, 10.0% or less, 8.0% or less, or 6.0% or less.

[0111] The rest of the coating except the above components is composed of Zn and impurities. The so-called impurities in the coating refer to components that are mixed into the coating due to various reasons in the manufacturing process, including raw materials, when the coating is manufactured, and are not intentionally added to the coating. In the coating, as impurities, elements other than the basic components and optional added components described above may also be contained in trace amounts within a range that does not hinder the effect of the present invention.

[0112] The chemical composition of the coating can be determined by dissolving the coating in an acid solution to which an inhibitor for inhibiting corrosion of the steel sheet is added, and measuring the obtained solution by ICP (high frequency inductively coupled plasma) emission spectrometry. The acid solution to which the inhibitor is added can be, for example, a 10 mass % hydrochloric acid solution to which 0.06 mass % inhibitor (manufactured by Asahi Chemical Industries, Ltd., IBIT) is added.

[0113] The thickness of the plating layer can be, for example, 3 to 50 μm. The amount of the plating layer applied is not particularly limited, but can be, for example, 10 to 170 g / m 2 In the present invention, the coating adhesion amount is determined by dissolving the coating in an acid solution to which an inhibitor for inhibiting corrosion of the steel sheet is added, and by the weight change of the coating before and after pickling and stripping. The coating thickness may be 5 μm or more, 10 μm or more, 15 μm or more, or 20 μm or more. The coating thickness may be 40 μm or less, or 30 μm or less. The coating adhesion amount may be 20 g / m per single side. 2 Above, 30g / m 2 Above, 40g / m 2 Above or 50g / m 2 The coating weight can be 150g / m per side. 2 Below, 130g / m 2 Below, 120g / m 2 Below or 100g / m 2 the following.

[0114] The roughness of the interface between the steel plate and the coating becomes the roughness of the surface of the steel plate, and therefore is 3.0 μm or less in Ra. If the adhesion of the coating is considered, Ra may be 2.5 μm or less or 2.0 μm or less. The roughness of the interface between the steel plate and the coating or the surface roughness of the steel plate measured by dissolving and removing the coating can be set.

[0115] It should be noted that the steel sheet of the present invention has the effect of improving LME resistance even if it is not galvanized. When the steel sheets that are not galvanized are welded to each other, LME cracks will not occur. However, even if a galvanized steel sheet is used on one side and a non-galvanized steel sheet is used on the other side for welding, molten galvanizing will be generated on the overlapping surface of the steel sheets during welding. Therefore, it is possible that the galvanized steel sheet surface that is not molten may come into contact with the galvanized steel sheet surface, causing LME cracks. In addition, when a non-plated steel sheet is welded using a welding electrode formed by spot welding a galvanized steel sheet, the galvanizing attached to the welding electrode melts and comes into contact with the steel sheet surface, causing LME cracks. If the steel sheet of the present invention is used as a non-plated steel sheet, even in such a case, the C concentration of the surface layer is low during welding, and the surface layer is a ferrite phase, so LME cracks can be suppressed.

[0116] The thickness of the steel plate and the plated steel plate of the present invention is not particularly limited. For example, it can be set to 0.6 to 3.2 mm. The thickness can be 0.8 mm or more or 1.0 mm or more. The thickness can be 3.0 mm or less, 2.6 mm or less, 2.4 mm or less, 2.2 mm or less, 2.0 mm or less, or 1.8 mm or less.

[0117] Next, the method for producing the steel sheet of the present invention will be described.

[0118] The steel sheet of the present invention can be obtained, for example, by a manufacturing method having the following steps: a casting step of casting molten steel with adjusted chemical composition to form a steel billet; a hot rolling step of hot-rolling the steel billet to obtain a hot-rolled steel sheet; a coiling step of coiling the hot-rolled steel sheet; a cold rolling step of cold-rolling the coiled hot-rolled steel sheet to obtain a cold-rolled steel sheet; a pretreatment step of brush-grinding the cold-rolled steel sheet; and an annealing step of annealing the pretreated cold-rolled steel sheet. Alternatively, after the hot rolling step, the steel sheet may be pickled without coiling and directly cold-rolled.

[0119] [Casting process]

[0120] The conditions of the casting step are not particularly limited. For example, after melting in a blast furnace, an electric furnace, or the like, various secondary melting processes are performed, and then casting is performed by a method such as ordinary continuous casting or casting by an ingot casting method.

[0121] [Hot rolling process]

[0122] The steel billet obtained by casting can be hot rolled to obtain a hot rolled steel plate. The hot rolling process is performed by reheating the cast steel billet directly or temporarily after cooling and hot rolling. In the case of reheating, the heating temperature of the steel billet can be, for example, 1100 to 1250°C. In the hot rolling process, rough rolling and finish rolling are usually performed. The temperature and reduction ratio of each rolling can be appropriately changed according to the desired metal structure and plate thickness. For example, the end temperature of the finish rolling can be 900 to 1050°C, and the reduction ratio of the finish rolling can be 10 to 50%.

[0123] [Coiling process]

[0124] The hot-rolled steel sheet can be coiled at a predetermined temperature. The coiling temperature can be appropriately changed according to the desired metal structure, for example, 500 to 800°C. The hot-rolled steel sheet can also be uncoiled before or after coiling to give a predetermined heat treatment to the hot-rolled steel sheet. Alternatively, the hot-rolled steel sheet can be pickled after the hot-rolling process without coiling and cold-rolled as described below.

[0125] [Cold rolling process]

[0126] After pickling the hot-rolled steel sheet, the hot-rolled steel sheet is cold-rolled to obtain a cold-rolled steel sheet. The cold-rolling reduction ratio can be appropriately changed according to the desired metal structure and plate thickness, for example, 20 to 80%. After the cold-rolling process, the steel sheet can be cooled to room temperature by air cooling, for example.

[0127] [Pretreatment process]

[0128] In order to make the thickness of the layer having the area ratio of the ferrite phase of 90% or more in the depth direction in the surface layer of the steel plate be 20 μm or more and the depth having the C concentration of 0.05% or less measured by GDS be 10 μm or more in the depth direction as described above, it is necessary to perform a predetermined pretreatment and then perform annealing.

[0129] The pretreatment includes grinding the surface of the cold-rolled steel sheet with a grinding brush (brush grinding treatment). As an example of a grinding brush that can be used, M-33 manufactured by Hotani Co., Ltd. can be cited. In this way, strain can be introduced without increasing the roughness of the surface. During grinding, a 1.0-5.0% aqueous solution of NaOH can be applied to the surface of the steel sheet. The brush pressure can be 0.5-10.0 mm and the rotation speed can be 100-1000 rpm. By controlling the brush grinding treatment to such coating liquid conditions, brush pressure, and rotation speed, decarburization is promoted in the annealing process described later, and a ferrite-stable structure can be effectively formed on the surface of the steel sheet.

[0130] [Annealing process]

[0131] After the pretreatment step, the cold-rolled steel sheet is annealed. Annealing is performed, for example, under a tension of 1 to 20 MPa. If tension is applied during annealing, strain can be more effectively introduced into the steel sheet, thereby promoting decarburization of the surface layer.

[0132] The holding temperature of the annealing process is set to 750-900°C. The holding temperature may be 770-870°C. By setting it in such a range, decarburization can be promoted, the C concentration of the surface layer can be reduced, and the ferrite phase can be stabilized. The heating rate to the holding temperature is not particularly limited, and can be 1-10°C / second.

[0133] The holding time at the holding temperature in the annealing process is set to 20 to 300 seconds. The holding time may be 30 to 250 seconds. By setting it within such a range, decarburization can be promoted, the C concentration in the surface layer can be reduced, and the ferrite phase can be stabilized.

[0134] The dew point of the atmosphere in the annealing process is set to -30 to 20°C. The dew point can be -10 to 5°C. The atmosphere can be, for example, N2-1 to 10 vol% H2, N2-2 to 4 vol% H2. If the dew point is too high or too low, a phase containing oxides such as Si, Mn, and Al is formed outside the steel sheet, and decarburization is not promoted. Furthermore, the mutual diffusion of the plating component and the steel component is sometimes hindered, and the plating property becomes insufficient.

[0135] According to the production method including the above-mentioned steps, decarburization is promoted in the surface layer of the steel sheet, and a steel sheet having a stabilized ferrite phase can be obtained.

[0136] <Method for producing plated steel sheet>

[0137] The plated steel sheet of the present invention can be obtained by a plating treatment step of forming an alloyed hot-dip galvannealed layer on the steel sheet produced as described above and an alloying treatment step.

[0138] The plating treatment process and the alloying treatment process can be carried out according to the hot dip plating method (also called the molten plating method) and the alloying treatment method known to those skilled in the art. The conditions of the plating treatment process and the alloying treatment process can be appropriately set by considering the chemical composition, thickness and adhesion amount of the desired coating. For example, it can be immersed in a hot dip galvanizing bath (also called a molten galvanizing bath) at 420 to 480°C with adjusted chemical composition for 1 to 10 seconds, and after dipping, it can be pulled out at 20 to 200 mm / second, and the coating adhesion amount can be controlled by N2 wiping gas. The alloying treatment can be carried out at 500 to 550°C for 10 to 60 seconds, for example.

[0139] The steel sheet and the plated steel sheet of the present invention are high in strength, have high LME resistance and dehydrogenation resistance, and therefore can be suitably used in a wide range of fields such as automobiles, home appliances, and building materials. It is particularly preferred to use it in the automotive field. Most of the steel sheets and plated steel sheets used for automobiles are spot welded, in which case LME cracks may become a significant problem. Therefore, when the steel sheet and the plated steel sheet of the present invention are used as steel sheets for automobiles, the effect of the present invention having high LME resistance can be appropriately exerted.

[0140] Example

[0141] Hereinafter, the present invention will be described in more detail by way of examples, but the present invention is not limited to these examples.

[0142] 《Example A》

[0143] First, the experiments preliminarily conducted by the inventors when the present invention was obtained are described. For steel plates (plate thickness 1.2 mm) with different Si and Al contents, spot welding was performed under the conditions shown in Table 1 for general alloyed hot-dip galvanized steel plates (plate thickness 1.6 mm), and LME cracks were confirmed during spot welding. The results are shown in Table 2. As shown in Table 2, it was confirmed that LME was suppressed by high Si-high Al steel.

[0144] Table 1

[0145]

[0146] Table 2

[0147]

[0148] Embodiment B

[0149] <Example 1>

[0150] (Preparation of Steel Plate Samples)

[0151] Molten steel adjusted to the chemical composition described in No. 1 of Table 3 was melted in a blast furnace and cast by continuous casting to obtain a steel billet. The obtained steel billet was heated to 1200°C, and hot rolled with the finishing temperature of the finish rolling at 950°C and the reduction rate of the finish rolling at 30% to obtain a hot-rolled steel sheet. The obtained hot-rolled steel sheet was coiled at a coiling temperature of 650°C, pickled, and then cold rolled at a reduction rate of 50% to obtain a cold-rolled steel sheet. The thickness of the cold-rolled steel sheet was set to 1.6 mm.

[0152] Next, the cold-rolled steel sheet was coated with a 2.0% aqueous solution of NaOH and subjected to a pretreatment of brush grinding. The brush grinding was performed using M-33 manufactured by Hotani Co., Ltd. as a grinding brush, with a brush reduction of 2.0 mm and a rotation speed of 600 rpm (Condition A in Table 4).

[0153] After the pretreatment step and before the annealing step, the surface roughness of the steel sheet was measured in accordance with JIS B0601: 2013. That is, 10 locations were randomly selected on the surface of the surface layer side, and the surface profile was measured at each location using a contact type surface roughness meter, and the arithmetic average roughness Ra obtained by arithmetically averaging the surface roughness of these locations was evaluated as follows.

[0154] Evaluation AA: 2.0μm or less

[0155] Evaluation A: more than 2.0 μm and less than 3.0 μm

[0156] Evaluation B: more than 3.0 μm

[0157] Then, the steel plate samples were prepared by annealing in a N2-4% H2 gas atmosphere in a furnace with an oxygen concentration of 20 ppm or less under the conditions of a dew point of 0°C, a holding temperature of 800°C, and a holding time of 100 seconds. The heating rate during annealing was set at 6.0°C / second up to 500°C and 2.0°C / second from 500°C to the holding temperature. The annealing was performed under a tension of 15 MPa.

[0158] <Examples 2 to 25, Comparative Examples 26 to 40>

[0159] The steel plate was manufactured in the same manner as in Example 1 except that the chemical composition was set to the composition described in Table 3 and the conditions of the pretreatment process and the annealing process were set to the conditions described in Table 4. It should be noted that the pretreatment of brush grinding was omitted in No. 39. In addition, in No. 40, the grinding brush used was D-100 manufactured by Hotani Co., Ltd. (Condition B in Table 4). D-100 is a brush with a grinding amount about twice that of M-33.

[0160] After annealing, the steel sheets whose "presence of alloyed hot-dip galvanizing layer" in Table 5 was "presence" were subjected to plating and alloying treatment to obtain alloyed hot-dip galvanized steel sheets. The plating treatment was performed by immersing in a hot-dip galvanizing bath (Zn-0.14% Al) at 450°C for 3 seconds. After immersion, the steel sheets were pulled out at 100 mm / sec, and the coating weight was controlled to 50 g / m by using N2 wiping gas. 2 The alloying treatment was performed at 520° C. for 30 seconds. The steel sheets whose “presence of alloyed hot-dip galvannealed layer” was “none” in Table 5 were not subjected to the plating treatment and the alloying treatment.

[0161]

[0162] Table 4

[0163]

[0164] ※The underlined characters are outside the range of the preferred production method.

[0165] (Surface tissue evaluation)

[0166] A sample cut into 30 mm × 30 mm was collected and GDS was measured 5 times in the plate thickness direction under the above conditions to find the depth at which the C concentration was 0.05% or less, which is shown in "C ≤ 0.05% depth" in Table 5. Here, the starting point of "depth" is the surface of the steel plate for unplated steel plates and the interface between the plating layer and the steel plate for plated steel plates.

[0167] In addition, a sample cut into 25 mm×15 mm was collected and etched with nitric acid etchant. The thickness of the layer in which the ferrite phase accounted for 90% or more was measured by the above method and is shown in "α phase thickness" in Table 5.

[0168] In addition, for the steel sheets that were not plated, the surface roughness of the steel sheets was measured by the same method as before annealing. For the steel sheets that were plated, the plating layer was removed using a 10 mass % hydrochloric acid solution to which 0.06 mass % inhibitor (manufactured by Asahi Chemical Industries, Ltd., IBIT) was added, and the surface roughness of the exposed steel sheets was measured by the same method as before annealing, which is shown in the "Roughness of the Steel Sheet Surface or Steel Sheet / Plating Interface" in Table 5.

[0169] (Tensile Strength Evaluation)

[0170] For each steel plate, a JIS No. 5 tensile test piece having a longitudinal direction perpendicular to the rolling direction was collected and subjected to a tensile test in accordance with JIS Z2241:2011 to obtain the tensile strength and evaluate it as follows.

[0171] Rating AAA: 1180MPa or above

[0172] Evaluation AA: 980MPa or more and less than 1180MPa

[0173] Evaluation A: 780MPa or more and less than 980MPa

[0174] (Evaluation of LME resistance)

[0175] Two samples cut into a size of 50 mm × 100 mm were collected from each steel plate. For these two samples, a dome-shaped welding electrode with a tip diameter of 8 mm was used to perform spot welding at a strike angle of 2°, a pressure of 4.0 kN, a power-on time of 0.5 seconds, and a power-on current of 12 kA to produce a welded joint. It should be noted that the steel plate that was not subjected to alloying hot-dip galvanizing was spot welded in combination with No. 2 that was subjected to hot-dip alloy coating.

[0176] Reference Figure 2, the evaluation of LME resistance is described. LME resistance is evaluated as follows based on the length of the crack 11 just outside the crimping portion of the weld 2 by spot welding two steel plates 1 overlapped. The so-called just outside the crimping portion of the weld refers to the portion outside the portion crimped by spot welding in the joint surface of the two steel plates, that is, the position near the crimped portion. In this embodiment, if the evaluation is A or above, it is judged that the LME resistance is excellent.

[0177] Rating AAA: 0μm

[0178] Evaluation AA: more than 0μm and less than 60μm

[0179] Evaluation A: 60 μm or more and less than 120 μm

[0180] Evaluation B: 120μm or more

[0181] (Dehydrogenation test)

[0182] A test piece of 80 mm × 50 mm in size was cut from each steel plate and electrochemically charged with hydrogen. The sample was charged with hydrogen at a constant current (cathode current density of 1 mA / cm 2 ) is powered on for 48 hours. After hydrogenation, the plated steel sheet is left to stand in an atmospheric atmosphere at room temperature for 48 hours. After a specified period of time, the amount of diffusible hydrogen contained in the plated steel sheet is determined by a temperature desorption method and evaluated as described below. It should be noted that in the temperature desorption method, the temperature is increased to 400°C at a heating rate of 100°C / h, and the sum of the amounts of hydrogen released from room temperature to 200°C is taken as the amount of diffusible hydrogen. In this embodiment, if the evaluation is A or above, it is judged to be excellent in dehydrogenation. When it is judged that both LME resistance and dehydrogenation resistance are excellent, it is judged to have solved the problem to be solved by the present invention.

[0183] Rating AAA: Less than 10% of the initial hydrogen amount

[0184] Evaluation AA: Less than 20% of the initial hydrogen amount

[0185] Evaluation A: Less than 50% of the initial hydrogen amount

[0186] Evaluation B: 50% or more of the initial hydrogen amount

[0187] Table 5 shows the results of each evaluation.

[0188] Table 5

[0189]

[0190] ※ Underlined elements are outside the scope of the present invention or do not provide the desired properties.

[0191] No. 26 is a comparative example in which the C content of the steel sheet is high. It is believed that since the C content of the steel sheet is high, decarburization of the surface layer does not proceed even by high dew point annealing. Therefore, the depth at which the C concentration is 0.05% or less and the thickness of the layer at which the area ratio of the ferrite phase is 90% or more do not increase. As a result, the LME resistance and dehydrogenation properties are poor.

[0192] No. 27 is a comparative example in which the Si content of the steel sheet is low. It is believed that since the Si content of the steel sheet is low, even if high dew point annealing is performed, decarburization of the surface layer does not proceed, and ferrite is not stabilized. Therefore, the depth at which the C concentration is 0.05% or less and the thickness of the layer at which the area ratio of the ferrite phase is 90% or more do not increase. As a result, the LME resistance and dehydrogenation resistance are poor.

[0193] No. 28 is a comparative example in which the Si content and the sum of the Si and sol.Al contents of the steel sheet are small. It is believed that since the Si content and the sum of the Si and sol.Al contents of the steel sheet are small, even if high dew point annealing is performed, decarburization of the surface layer does not proceed, and ferrite is not stabilized. Therefore, the depth at which the C concentration is 0.05% or less and the thickness of the layer at which the area ratio of the ferrite phase is 90% or more do not increase. As a result, the LME resistance and dehydrogenation resistance are poor.

[0194] No. 29 is a comparative example in which the Si content of the steel sheet is high. It is believed that since the Si content of the steel sheet is high, external oxidation proceeds even when high dew point annealing is performed, and oxides (scale) are formed on the surface layer of the steel sheet, which inhibits decarburization on the outermost surface. Therefore, the depth at which the C concentration is 0.05% or less does not increase. As a result, the LME resistance and dehydrogenation resistance are poor.

[0195] No. 30 is a comparative example in which the sol. Al content of the steel sheet is small. It is believed that since the sol. Al content of the steel sheet is small, even if high dew point annealing is performed, decarburization of the surface layer does not proceed, and ferrite is not stabilized. Therefore, the depth at which the C concentration is 0.05% or less and the thickness of the layer at which the area ratio of the ferrite phase is 90% or more do not increase. As a result, the LME resistance and dehydrogenation resistance are poor.

[0196] No. 31 is a comparative example in which the sol. Al content and the sum of the Si and sol. Al contents of the steel sheet are small. It is believed that since the sol. Al content and the sum of the Si and sol. Al contents of the steel sheet are small, even if high dew point annealing is performed, decarburization of the surface layer does not proceed, and ferrite is not stabilized. Therefore, the depth at which the C concentration is 0.05% or less and the thickness of the layer at which the area ratio of the ferrite phase is 90% or more do not increase. As a result, the LME resistance and dehydrogenation resistance are poor.

[0197] No. 32 is a comparative example in which the sol. Al content of the steel sheet is high. It is believed that since the sol. Al content of the steel sheet is high, external oxidation proceeds even when high dew point annealing is performed, and oxides (scale) are formed on the surface layer of the steel sheet, which inhibits decarburization on the outermost surface. Therefore, the depth at which the C concentration is 0.05% or less does not increase. As a result, the LME resistance and dehydrogenation resistance are poor.

[0198] No. 33 is a comparative example in which the sum of the contents of Si and sol. Al in the steel sheet is small. It is believed that since the sum of the contents of Si and sol. Al in the steel sheet is small, even if high dew point annealing is performed, decarburization of the surface layer does not proceed, and ferrite is not stabilized. Therefore, the depth at which the C concentration is 0.05% or less and the thickness of the layer at which the area ratio of the ferrite phase is 90% or more do not increase. As a result, the LME resistance and dehydrogenation resistance are poor.

[0199] Regarding No. 34, it is considered that due to the low dew point during annealing, a phase containing oxides such as Si, Mn, and Al was formed on the outside of the steel sheet during annealing, and the mutual diffusion of the plating components and the steel components was hindered during the plating process. As a result, appropriate plating could not be obtained.

[0200] Regarding No. 35, it is considered that since the dew point during annealing was low, a phase containing oxides such as Si, Mn, and Al was formed on the outside of the steel sheet during annealing, decarburization was not promoted, and ferrite was not stabilized. Therefore, the depth at which the C concentration was 0.05% or less and the thickness of the layer at which the area ratio of the ferrite phase was 90% or more did not increase.

[0201] Regarding No. 36, it is considered that since the dew point during annealing was high, a phase containing oxides such as Si, Mn, and Al was formed on the outside of the steel sheet during annealing, decarburization was not promoted, and ferrite was not stabilized. Therefore, the depth at which the C concentration was 0.05% or less and the thickness of the layer at which the area ratio of the ferrite phase was 90% or more did not increase.

[0202] Regarding No. 37, it is considered that due to the high dew point during annealing, a phase containing oxides such as Si, Mn, and Al was formed on the outside of the steel sheet during annealing, and the mutual diffusion of the plating components and the steel components was hindered during the plating process. As a result, appropriate plating could not be obtained.

[0203] Regarding No. 38, it is considered that the holding temperature during annealing was low, so decarburization was not sufficiently promoted during annealing. Therefore, the depth of the C concentration of 0.05% or less and the thickness of the layer with an area ratio of the ferrite phase of 90% or more did not increase. As a result, the LME resistance and dehydrogenation properties were poor.

[0204] Regarding No. 39, it is considered that the holding temperature during annealing was high, so decarburization was not sufficiently promoted during annealing. Therefore, the depth of the C concentration of 0.05% or less and the thickness of the layer with an area ratio of the ferrite phase of 90% or more did not increase. As a result, the LME resistance and dehydrogenation properties were poor.

[0205] Regarding No. 40, it is thought that the holding time during annealing was short, so decarburization was not sufficiently promoted during annealing. Therefore, the depth of the C concentration of 0.05% or less and the thickness of the layer with an area ratio of the ferrite phase of 90% or more did not increase. As a result, the LME resistance and dehydrogenation properties were poor.

[0206] Regarding No. 41, it is considered that since brush grinding in the pretreatment process was not performed, strain was not introduced into the surface of the steel sheet, and decarburization did not proceed during annealing. Therefore, the depth of the C concentration of 0.05% or less and the thickness of the layer with an area ratio of the ferrite phase of 90% or more did not increase. As a result, the LME resistance and dehydrogenation properties were poor.

[0207] Regarding No. 42, it is believed that since a brush with a large grinding amount was used in the brush grinding in the pretreatment process, the roughness of the steel plate surface increased, and the ferrite phase was unstable. Therefore, the thickness of the layer with an area ratio of ferrite phase of 90% or more did not increase. As a result, the LME resistance and dehydrogenation property were poor.

[0208] On the other hand, No. 1 to 25 are examples of the present invention, and have high LME resistance and dehydrogenation properties. In examples where the depth of the C concentration is 0.05% or less and the thickness of the layer with an area ratio of the ferrite phase of 90% or more is large, particularly excellent LME resistance is confirmed.

[0209] Industrial Applicability

[0210] According to the present invention, a high-strength steel sheet and a plated steel sheet having high LME resistance and dehydrogenation resistance can be provided, and the steel sheet and the plated steel sheet can be suitably used for applications such as automobiles, home appliances, and building materials, especially automobile applications. Therefore, the present invention is an invention with extremely high industrial applicability.

[0211] Description of Reference Numerals

[0212] 1 Steel Plate

[0213] 2 Welding section

[0214] 11 Cracks on the outer side of the crimped part

Claims

1. A steel plate having a tensile strength of 780 MPa or more, characterized in that: The chemical composition by mass% contains: C:0.05~0.40%、 Si: 0.7-3.0%, Mn: 0.1-5.0%, Sol.Al: 0.7~2.0%, P: 0.030% or less, S: 0.030% or less, N: 0.010% or less, B:0~0.010%、 Ti: 0~0.150%, Nb: 0~0.150%, V:0~0.150%、 Cr:0~2.00%、 Ni: 0-2.00%, Cu: 0-2.00%, Mo: 0-1.00%, W:0~1.00%、 Ca: 0~0.100%, Mg: 0~0.100%, Zr:0~0.100%、 Hf: 0~0.100%、 REM: 0~0.100%, The rest is Fe and impurities. The total content of Si and sol.Al is 1.8% or more. In the depth direction from the surface of the steel sheet, the depth at which the C concentration measured by GDS is 0.05% or less is 10 μm or more. In the depth direction from the surface of the steel sheet, the thickness of the layer having an area ratio of ferrite phase of 90% or more is 20 μm or more, The surface roughness of the steel plate is 3.0 μm or less in Ra.

2. The steel plate according to claim 1, characterized in that: In the depth direction from the surface of the steel sheet, the depth at which the C concentration measured by GDS is 0.05% or less is 20 μm or more.

3. The steel plate according to claim 1, characterized in that: The thickness of the layer having an area ratio of the ferrite phase of 90% or more in the depth direction from the surface of the steel sheet is 30 μm or more.

4. The steel plate according to claim 1, characterized in that: In the depth direction from the surface of the steel plate, the depth where the C concentration measured by GDS is 0.05% or less is 20 μm or more, and in the depth direction from the surface of the steel plate, the thickness of the layer where the area ratio of the ferrite phase is 90% or more is 30 μm or more.

5. An alloyed hot-dip galvanized steel sheet, characterized in that: At least a portion of the surface of the steel sheet according to any one of claims 1 to 4 is provided with a galvannealed layer, wherein the galvannealed layer contains, by mass%, 0 to 1.5% Al and 3 to 15% Fe, and the remainder is Zn and impurities.

6. The alloyed hot-dip galvannealed steel sheet according to claim 5, characterized in that: The roughness of the interface between the steel sheet and the galvannealed layer in the cross section of the galvannealed steel sheet is 2.0 μm or less in terms of Ra.

Citation Information

Patent Citations

  • Steel sheet, hot-dip zinc-coated steel sheet, and alloyed hot-dip zinc-coated steel sheet

    WO2019116531A1

  • Steel sheet

    WO2020218575A1